0628 Epilepsy Control and Night Sleep Duration and Afternoon Siesta. (25th May 2022) - Al-Abri, Mohammed; Al-Asmi, Abdullah
Abstract: Introduction: The relationship between sleep and epilepsy has long been recognized but understanding the association between seizure control and sleep duration is not well explored. The study aims to describe the sleep habits in people with epilepsy (PwE) and explore the association between sleep habits, particularly afternoon napping and level of seizure control and anti-epileptic drugs (AEDs). Methods: this is a cross-sectional study of adult epilepsy patients attending neurology clinic. Sleep parameters are measured using actigraphy for one week and home sleep apnea testing to rule out obstructive sleep apnea (OSA). Results: total of 250 PwE were screened and 129 patients (male & female) completed the study with mean age of 29.75 ± 9.18 years and mean body mass index (BMI) of 27.12 kg/m2. There was significant association between night sleep duration and time of wake up and number of AEDs (adjusted R2=0.026, P=0.03 & P=0.04 respectively). There is also significant association between number of seizures per night and afternoon napping (adjusted R2=0.043, P=0.05). Other sleep parameters did not reveal any significant association with level of epilepsy control neither with number of AEDs (P>0.05). Conclusion: The study described that PwE with uncontrolled epilepsy on multiple AEDs are practicing sleep habits that involved longer afternoon napping and shorter sleep duration. Support (If Any): Sultan Qaboos University